Approach for channel reservation and allocation to improve quality of service in vehicular communications. Issue 2 (1st June 2014) - Saritha, Vankadara; Madhu Viswanatham, Vankadara
Abstract : Channel allocation plays an important role in next generation of wireless networks that require huge bandwidth support for various applications. It became very interesting and important research area in vehicular ad hoc network (VANET) as the channel allocation procedure needs to be efficient as the frequency of handoff is high because of the high mobility of the nodes. So, the authors propose a channel allocation algorithm that utilises channel reuse technique, channel borrowing process and the speed of the vehicle to reserve the channel for handoff calls to improve quality of service (QoS) in VANET. The calls are categorised as real‐time originating calls, real‐time handoff calls, non‐real‐time originating calls, non‐real‐time handoff calls and non‐real‐time transfer calls, and queue is maintained for non‐real‐time originating calls, which leads to non‐real‐time transfer calls. The channel borrowing process is incorporated only for real‐time originating calls and real‐time handoff calls. The proposed system is modelled using two‐dimensional Markov model. The proposed algorithm is simulated and evaluated in terms of QoS parameters as blocking probability, dropping probability and handoff latency. The performance is tested with varying system load, varying number of channels and is compared with legacy systems like cooperative reservation of service channels, CRaSCH, and a new dynamic channel allocation strategy which combines channel reservation with new call queuing, RQS.